Community Engagement Alliance (CEAL) Against COVID-19 Disparities: Academic-community partnership to support workforce capacity building among Arizona community health workers - Jiménez, Dulce J.; Gomez, Omar; Meraz, Ruby; Pollitt, Amanda M.; Evans, Linnea; Lee, Naomi; Ignacio, Matt; Garcia, Katherine; Redondo, Richard; Redondo, Floribella; Williamson, Heather J.; Oesterle, Sabrina; et al. (Frontiers in Public Health, 2023)
The COVID-19 pandemic has both highlighted and worsened existing health inequities among communities of color and structurally vulnerable populations. Community Health Workers, inclusive of Community Health Representatives (CHW/Rs) have entered the spotlight as essential to COVID-19 prevention and control. To learn about community experiences and perspectives related to COVID-19 and inform CHW/R workforce capacity building efforts, a series of focus groups were conducted with CHW/Rs throughout Arizona at two time points in 2021. Throughout the data collection and analysis process, researchers and community partners engaged in ongoing and open dialogue about what CHW/Rs on the ground were reporting as priority community concerns, needs, and challenges. Thus, CHW/Rs informed the development of culturally and linguistically relevant health education messages, materials, and training for CHW/Rs. In this community case study, we detail the efforts of partnership between a statewide CHW professional association and an academic research team that facilitated rapid decision-making and knowledge sharing to create community-grounded tools and resources supportive of CHW/R workforce capacity building in the context of the COVID-19 pandemic.